Analisis Pengaruh Faktor-Faktor Sosial Terhadap Keputusan Pembelian Produk Teh Botol Sosro - Febrianti, Erika; Rahmawati, Ita; Sa’adah, Lailatus (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
The purpose of this research is to find out whether there is an influence of social factors on the purchasing decision of Sosro Botol tea products. The variables in this study include family, reference groups, social roles and status, purchasing decisions. The method used in this research is a quantitative method. The population in this study is unlimited while the sample is 100 respondents using a purposive sampling technique. Data were collected using the questionnaire method, which were then analyzed using multiple regression analysis using SPSS version 26. The results showed that partially family variables had no significant effect on purchasing decisions for Sosro bottled tea products, while reference group variables partially also had a significant effect on the purchasing decision of Sosro Botol tea, and on the role and social status variables, there is no significant effect on the Sosro Botol tea purchasing decision. Simultaneously, family variables, reference groups, roles and social status have no significant effect on the Sosro Botol tea purchasing decision.